Analisis Nilai-Nilai Karakter Konservasi Pada Buku Apel Emas Sebagai Bahan Ajar Berbasis Kearifan Lokal - Listiani, Elis; Wuryastuti, Sri (Didaktika, 2022)
Environmental conservation is an effort to maintain, care for and protect the environment from damage. Currently there has been a lot of environmental damage, therefore it is necessary to instill the values of conservation character by introducing and instilling them through the educational process, one which is to students in elementary schools. In order to make the content of the material easier to understand, learning is packaged through contextual learning with teaching materials based on students' backgrounds. The purpose of research is to describe the values of the conservation character from the Apel Emas [Golden Apple] storybook for make teaching materials about environmental conservation, and the background of students as the basis for preparing teaching materials. The results of this analysis will then be compiled in a thematic teaching material based on local wisdom in class IV Theme 3 Caring for Living Creatures, Sub-theme 1, Learning 3. This study uses content analysis methods with data analysis techniques. Based on the results of the analysis found 22 data fragments of stories that have conservation character values, namely: 1) inspirational values totaling 3 fragments of stories; 2) the humanist value is 1 piece of the story; 3) the value of caring is 7 fragments of the story; 4) innovative value of 1 story fragment; 5) creative value of 6 pieces of story; 6) supportive value 1 piece of story; 7) honest value of 1 story fragment and 8) fair value of 2 story fragments, and students' perceptions of teaching materials that are more colorful with pictures and short stories in them. The forms of teaching materials consist of: short stories, handouts, interview sheets, and LKPD to plant local plants. From the results of this analysis, it can be seen that the Apel Emas book can be used as thematic teaching materials in elementary schools